Impacts of the substrate medium on tomato yield and fruit quality in soilless cultivation - Tzortzakis, Nikos G.; Economakis, C. D. (My University, 2008)
The performance and suitability of different substrates for the soilless culture of tomato plants (Lycopersicum esculentum Mill., cv. Belladona) were studied over a 5-month period in a closed soilless culture system employing five different substrates (perlite, pumice or maize and their mixtures with 50% shredded maize stems in an unheated glasshouse). Plants grown in a maize stem-containing medium produced earlier fruits, followed by pumice. Plants grown in pumice and perlite substrates obtained lower total yield; a higher yield was associated with the addition of maize shredded stems. Pumice + 50% maize and 100% maize produced higher total number of fruits per plant. Fruit quality parameters such as mean fruit weight, fruit firmness, total soluble solids, titratable acidity, ascorbic acid and carotenoids were influenced by the treatment, while EC, pH and dry matter content were not. The results suggest that the addition of maize in perlite and pumice could improve inorganic substrates properties for tomato soilless culture, leading to higher yields and better fruit quality.
Keywords: Carotenoids; Earliness; Fruit quality; Organic materials; Perlite; Pumice; Soilless culture; Tomato; Yield